STRATEGI PENERAPAN LINGKUNGAN BAHASA ARAB DALAM MENINGKATKAN KEMAHIRAN BERBAHASA ARAB DI PESANTREN MODERN DARUSSALAM - Rahim Marpaung, Willi; Lubis, Zulfahmi (Inspiratif Pendidikan, 2023)
Improving the Arabic language of these students needs to be considered in the strategy of implementing the language environment, in this case the strategy of implementing the Arabic language environment is a problem in increasing Arabic language proficiency, especially in the Arabic skills of the students of Modern Darussalam Langkat Islamic Boarding School which must be achieved not only from speaking skills and writing only, but the four language skills in students which are speaking, listening, writing, and reading skills. Furthermore, the purpose of the researchers to conduct this study was to describe or describe the strategy for implementing the Arabic language environment in increasing the Arabic language proficiency of Islamic boarding school students in Modern Darussalam, and the researchers used qualitative research methods with observation, interview, and documentation research techniques. The object of research is the students of the Modern Darussalam Langkat Islamic Boarding School, thus the researchers obtained the results of this study, namely the strategy for implementing the Arabic language environment is the responsibility of the school management and all dormitory administrators which involve all students at the Darussalam Modern Islamic Boarding School. Thus, all parties will feel the language environment and wholeheartedly support all programs related to the language environment. Then the strategy for implementing the Arabic language environment is by carrying out various kinds of language activities and also forming Munazzamah (foster siblings), so that students’ Arabic language proficiency can increase through the strategy for implementing the Arabic language environment.